Enforcing consumer and capital markets law : the Diesel emissions scandal / edited by Beate Gsell, Thomas M. J. Möllers. - Gsell, Beate; Möllers, Thomas M. J. (Intersentia, 2020)
Enforcing Consumer and Capital Markets Law: The Diesel Emissions Scandal is an international and intradisciplinary work. On the example of one topical and global collective damage event with far reaching consequences for both consumers and investors, this work critically analyses the various approaches of public and private law enforcement and their effectiveness across several jurisdictions, namely those of Austria, Denmark, France, Germany, England and Wales, Italy, Lithuania, the Netherlands, Portugal, Australia, Brazil, China and the United States of America. Based on decided and pending cases, the book demonstrates to what extent public authorities, but also private claimants, can take effective steps against the violation of their rights in their respective jurisdictions. The following is examined: law enforcement by public institutions, law enforcement by private parties and overlaps as well as hybrids and connections between both areas. A particular focus is given to collective redress, that is representative actions and model case proceedings. Comments from renowned practitioners sharing their experiences are included throughout the book. Separate concluding comparative chapters have two different aims: A comparative analysis of the legal solutions with a supranational European Union level focus provides invaluable insights into best practices and effectiveness. In addition, an intradisciplinary comparison assesses and evaluates the effectiveness of consumer law vs capital markets law mechanisms. Furthermore mechanisms of competition law and company law are taken into account.